Descriptors and Perception of Dyspnea in African-American Asthmatics - Trochtenberg, D. Scott (2007)
OBJECTIVE: This study explores self-reported perception of asthma symptoms in African-Americans. METHODS: Qualitative methodology was used to analyze the responses from African-Americans within focus groups from Nashville, Tennessee. RESULTS: Common symptoms were chest tightness, “breathing problems,” and wheeze. Less commonly reported symptoms included cough, chest pain, dizziness, sweating, and “short of breath.” A single participant reported nocturnal wheezing. CONCLUSIONS: This study provides insight into the descriptors and perception of asthma symptoms in African-Americans. Understanding the descriptors of symptoms and disease severity in African-American patients may lead to more accurate diagnosis, treatment, and reduced mortality within this high-risk population.